Museum, heritage, and city: layers of meaning in Paraty (Cadernos de Sociomuseologia, 2014)
The role of museums in strategies for preservation of historic cities included in the category of heritage is the guiding thread of this text which, on the other hand, recognizes that these cities are themselves and one time, as well as museums, places of memory and forgetting, power and resistance. The museums here are understood as social practices, havens for relationship and storytelling devices that are constructed through spatiality, temporality, images, information, experiences and cohabitation handled simultaneously as goods, representations and cultural events. The study focuses on a museum located in a city-heritage, the Museum of Sacred Art in the city of Paraty. Keywords: conservation; museums; heritage; urban heritage